The Effectiveness of Concrete Poetry as a Strategy to Teach Reading Comprehension to Children with Asperger Syndrome - Chia, Noel Kok Hwee; Tee Ng, Angie Gek (Journal of the American Academy of Special Education Professionals, 2009)
Asperger Syndrome, originally known as autistic psychopathy, was formally defined in 1944 by Hans Asperger, an Austrian pediatrician. The disorder causes difficulties in understanding the world and interacting with others. It impacts motor activities, social functioning and language learning, especially in the area of reading and listening comprehension. Many intervention strategies have been developed to help such children to tackle their comprehension deficits. In this study, the authors introduced concrete poetry as a strategy to teach reading comprehension to children with Asperger Syndrome.